PENGARUH MINAT BELAJAR DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR KOMPUTER AKUNTANSI SMK NEGERI 4 PEKANBARU - Cindy Sofia Nanda; Caska Caska; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the influence of interest in learning and learning discipline on learning outcomes of accounting computer at SMK Negeri 4 Pekanbaru. This study used a quantitative descriptive method and the population in this study were 106 students of class XI and XII accounting, using purposive sampling technique. The data analysis technique used was the F test, the coefficient of determination (R2), and the multiple linear regression test. The results in this study are that interest in learning affects the learning outcomes of accounting computer where the tcount is 2.859 ≥ 2.016 and a significant value is 0.006 ≤ 0.05. Learning discipline has an effect on the learning outcomes of accounting computers where the tcount is 3.177 ≥ ttable 2.016 and a significant value is 0.003 ≤ 0.05. Simultaneously there is a significant influence between interest in learning and learning discipline where the value of Fcount 30.698 ≥ Ftable is obtained and a significant value is 0.000 ≤ 0.05. Multiple linear regression equation Y = 39,868 + 5.028 X1 + 5,730 X2. The results of the coefficient of determination (R2) obtained a value of 0.543 or 54.3%, meaning that this means that the variables of interest in learning (X1), learning discipline (X2) together contribute to learning outcomes by 54.3%, and the rest ( 45.7%) influenced by other factors not included in the study.Key Words: Learning Outcomes, Interest In Learning, Learning Discipline